2012
DOI: 10.1182/blood-2011-03-343608
|View full text |Cite
|
Sign up to set email alerts
|

The CXCR7 chemokine receptor promotes B-cell retention in the splenic marginal zone and serves as a sink for CXCL12

Abstract: IntroductionLocalization and retention of B cells in the marginal zone (MZ) depends on antigenic specificity, 1,2 interactions between integrins and their receptors, 3 and signaling by the lysophospholipid, S1P, through the S1P 1 receptor. 4 Although MZ B cells are considered nonrecirculatory, exposure to cognate Ag or bacterial products causes them to relocalize from the MZ to the splenic white pulp, 4 providing for efficient delivery of captured Ags to follicular dendritic cells. 5 Although no direct evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 23 publications
(33 reference statements)
5
60
0
Order By: Relevance
“…[39][40][41][42] Although less is known regarding the role of CXCR7, 43,44 CXCR5 and CXCR4 regulate the development and the trafficking of B cells within the GC. 45 In normal lymphoid tissue, CXCR4 is highly expressed in the dark zone of the GC, attracting the centroblasts, whereas CXCR5 expression is in the light zone and contributes to attracting B cells to the area and is then downregulated during plasmacytic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42] Although less is known regarding the role of CXCR7, 43,44 CXCR5 and CXCR4 regulate the development and the trafficking of B cells within the GC. 45 In normal lymphoid tissue, CXCR4 is highly expressed in the dark zone of the GC, attracting the centroblasts, whereas CXCR5 expression is in the light zone and contributes to attracting B cells to the area and is then downregulated during plasmacytic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause proliferative and pro-survival effects in the lymphoma cells. As pharmacological blockage of the interaction of CXCL12 with CXCR7 leads to retention of marginal zone B cells in the splenic marginal zone, 56 it might be speculated that CXCR7-CXCL12 interaction is essential for the homing process of MALT lymphoma and extranodal diffuse large B-cell lymphoma cells to the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…At these sites, B cells gain access to various molecular factors that drive both the differentiation and survival of the MZ B cell subset (38). Proteins encoded by S1pr3 and Cxcr7 (named sphingosine-1-phosphate receptor-3 [S1PR 3 ] and CXCR7, respectively) have been shown to play specific roles in the migration and/or retention of B cells within the MZ niche (4,46,47). Our previous study showed that NOD MZ B cells had an increased capacity for migration toward sphingosine-1-phosphate (S1P) compared with those from B6 mice in chemotaxis assays, which was dependent on their elevated expression of S1PR 3 (12).…”
Section: Nod B Cells Have Enhanced Capacity To Migrate Into Mz Nichementioning
confidence: 99%
“…CXCR7 acts as a scavenging receptor that binds and degrades CXCL12 and CXCL11, preventing them from interacting with CXCR4 and CXCR3, respectively (48,49). A recent report by Wang et al (47) demonstrated that CXCR7 plays a role in guiding B cells to the MZ by restricting CXCL12 from binding to CXCR4 and that blocking CXCR7 with small molecule inhibitors decreased localization of MZ B cells within this niche. Consistent with their higher gene expression of Cxcr7 (Fig.…”
Section: Nod B Cells Have Enhanced Capacity To Migrate Into Mz Nichementioning
confidence: 99%